Colonialism and Malay masculinity: Malay satire as observed in the novel Kawin-Kawin - Noritah Omar, (Universiti Kebangsaan Malaysia, 2006)
This article evaluates the novel Kawin-Kawin as a satire, and as a mode for forming social criticism on Malay society. An assessment of such a genre must consider the target audience and the Islamic cultural context of the novel. The discussion seeks to identify male domination that through legal frameworks such as the mut’ah, and reduces women to objects of male sexual pleasure. The reading of cultural domination includes what may perhaps be considered a postcolonial analysis of notions of hegemonic masculinity, and of colonialism pertaining to Malay writings. Both notions share similarities in their functions and effects on marginalized groups and are debated under the categories of Islam and women. The discussion concludes with an evaluation of the literariness of Malay writings and the need for their detachment from Western literary frameworks if they are to break away from lingering aspects of colonialism